Improvement of filtration process for nucleocapsid protein of Newcastle disease virus - Ahmad Raus, Raha; Awang, Rabiatul Adawiyah; Mel, Maizirwan; Yusoff, Khatijah (2009)
This research was mainly focusing on improving the purification process for recombinant nucleocapsid (NP) protein of Newcastle disease virus (NDV). In this study, several conditions of the independent variables that affect the microfiltration process such as the temperature, transmembrane pressure (TMP), and viscosity were observed. A microporous membrane screening using two different sizes of membrane which are 0.1μm and 0.45μm was performed before further improvement on NP protein filtration was carried out. It turned out to be that 0.45μm membrane gave higher yield of NP protein than that of 0.1μm membrane. Thus, 0.45μm membrane was used to improve the filtration process for NP protein. Based on the Full Factorial Design (STATISTICA 8.0, Statsoft, Inc.), eight sets of experiment were designed to identify the best conditions for the NP protein filtration. From these experiments, the optimal conditions that gave the highest yield of NP protein are; TMP 4.5psi, viscosity 2.39cP at 4ºC. Based on ANOVA (analysis of variance), all the independent variables studied do not significantly affect the purification of NP protein. However, based on the lowest p value for each variable corresponding to each response, temperature has the largest effect for the NP protein yield.